Hybrid minigene splicing assay verifies the pathogenicity of a novel splice site variant in the COL1A1 gene of a chinese patient with osteogenesis imperfecta type I. Issue 12 (December 2019) - Lin, Yuxiang; Li, Xiaoli; Huang, Xinghua; Zheng, Dezhu; Liu, Yichu; Lan, Fenghua; Wang, Zhihong
Highlights: We identified a novel splice site variant in the COL1A1 gene. This study extended the genetic mutation about osteogenesis imperfecta. We demonstrated that combined applications of NGS, bioinformatics and HMSA are comprehensive and effective methods for diagnosis and aberrant splicing study of osteogenesis imperfecta. Abstract: Background: Osteogenesis imperfecta (OI) is a rare genetic bone disease associated with brittle bones and fractures. Among all known types, OI type I is the most common type and characterized by increased bone fragility, low bone mass, distinctly blue-gray sclera, and susceptibility to conductive hearing loss beginning in adolescence. Mutations in genes encoding type I collagen ( COL1A1 and COL1A2 ) contribute to the main pathogenic mechanism of OI. Methods: Subtle mutation of the COL1A1 gene in the proband was detected by targeted next-generation sequencing (NGS) and confirmed by Sanger sequencing. We then assessed the effect of the mutation on the splicing of the COL1A1 gene by bioinformatics prediction and hybrid minigene splicing assay (HMSA). Results: A novel splice site mutation c.1821+1 G > C was discovered in the proband by NGS and further confirmed by Sanger sequencing, which was also simultaneously identified from the proband's mother and elder sister. Bioinformatics predicted that this mutation would result in a disappearance of the 5′ donor splice site in intron 26, thereby leading to abnormal splicing and generation of premature stop codon. The follow-up experimental data generated by HMSA was consistent with this prediction. Conclusion: Our study identified a novel splice site mutation that caused OI type I in the proband by abnormal splicing and demonstrated that combined applications of NGS, bioinformatics and HMSA are comprehensive and effective methods for diagnosis and aberrant splicing study of OI.